A two-phase multicast routing in MANETs using Steiner connected dominating core sets. (18th November 2005) - Wang, Chu-Fu; Jan, Rong-Hong
Multicast communication is a point to multipoint transmission that occurs when data is to be delivered to a subset of nodes in a computer network. Because multicast communications can save network bandwidth when delivering data to multiple destinations, many researchers have given much attention to multicast routing problems. An ad hoc network is a multihop wireless network with highly dynamic behaviour. Because an ad hoc network's topology changes frequently, multicast routing in such a network is more complicated than in wired networks. In this paper, a two phase multicast routing scheme using Steiner Connected Dominating Core Sets (SCDCS) is proposed to accommodate the dynamic nature of ad hoc networks. The problem of finding the minimum SCDCS is called the Steiner Connected Domination Problem (SCDP). Two heuristic algorithms are proposed to compute the approximate SCDP solution. Some simulations are also made for evaluating the performance of the proposed methods. Two polynomial time exact algorithms to solve the proposed problem on trees with two types of dominating functions are given.